2019
DOI: 10.1108/ecam-05-2018-0211
|View full text |Cite
|
Sign up to set email alerts
|

Developing a benchmarking system for architecture design firms

Abstract: Purpose The construction industrys business model is mainly based on the interaction among the architecture office, the engineering office and the construction company. The performance and practices of architects offices, unlike those of the other actors, are difficult to characterize and there have been few studies on these issues. To better understand architects' performance, the purpose of this paper is to develop a benchmarking tool based on real practices identified by managers of Chilean architecture off… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 25 publications
0
19
0
Order By: Relevance
“…Previous studies have identified several criteria for the performance of architects. The objectives of project stakeholders should be identified to achieve a successful project (Afolabi et al, 2018;Salvatierra et al, 2019). To do so, architects should work closely with their clients to learn the project objectives that they prioritise (Adinyira and Dafeamekpor, 2015;Marisa, 2018).…”
Section: Performance Of Architectsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have identified several criteria for the performance of architects. The objectives of project stakeholders should be identified to achieve a successful project (Afolabi et al, 2018;Salvatierra et al, 2019). To do so, architects should work closely with their clients to learn the project objectives that they prioritise (Adinyira and Dafeamekpor, 2015;Marisa, 2018).…”
Section: Performance Of Architectsmentioning
confidence: 99%
“…Therefore, the ability to identify and prioritise project objectives is an important criterion for assessing the performance of architects. Salvatierra et al (2019) argued that the works of architects are evaluated on the basis of the quality of their designs. Given that a good design quality should be achieved in construction projects, the performance of architects should consider the quality and aesthetic value of their designs (Al-Saggaf, Nasir and Hegazy, 2020).…”
Section: Performance Of Architectsmentioning
confidence: 99%
See 1 more Smart Citation
“…This research proposes a tool to assess management practices in the design phase of construction projects; then, the study identifies implementations gaps, it provides benchmarks with other projects, and it improves the design process through a taxonomy of lean design management practices. been studied to evaluate its performance [7], to implement integrated management systems and visual management tools [8], as well as to optimize this process [6].Technological tools have great potential to improve the performance of projects, particularly in the design phase. However, the problems generated in the design of construction projects cannot be solved with technology alone but require an understanding of the social phenomena related to the processing of individual and collective information [9].…”
mentioning
confidence: 99%
“…This research proposes a tool to assess management practices in the design phase of construction projects; then, the study identifies implementations gaps, it provides benchmarks with other projects, and it improves the design process through a taxonomy of lean design management practices. been studied to evaluate its performance [7], to implement integrated management systems and visual management tools [8], as well as to optimize this process [6].…”
mentioning
confidence: 99%